SINTESIS NANOPARTIKEL PERAK TERMODIFIKASI KITOSAN SECARA REDUKSI KIMIA: REVIEW ARTIKEL - Saputra, Aswin Caesar; Alimuddin, Alimuddin; Arif, Syaiful (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Nanoparticle is a compound particle that is synthesized in sizes ranging from 1-100 nanometers. Some things that need to be considered in the synthesis of silver nanoparticles are from their size, shape and morphology. In chemical methods, nanoparticles are made by reducing Ag+ ions, so that reducing agents and stabilizers play an important role in synthesis. Different reducing agents will affect the size of the resulting nanoparticles. Based on the literature review, a popular method used to synthesize silver nanoparticles is to use sodium borohydride as a silver nitrate reductor which has the advantage of being able to reduce and stabilize silver nitrate well, if modified with chitosan, silver nanoparticles formed will be more stable and can last longer. Based on previous research, chitosan-modified silver nanoparticles were used for antibacterial activity tests conducted against Escherichia coli and Staphylococcus aureus bacteria and for colorimetric detection of Hg2+ metal in water, where there was a color change in silver nanoparticles from yellow to colorless which showed high selectivity of chemical sensors to detect target analytes. Keywords : Silver Nanoparticles, Reducing Agents, Stabilizer, Chemical sensors.